A modified model of surface temperature inversion based on Landsat 8 remote-sensing data and measured data. Issue 19 (2nd October 2018) - Fu, Ying; Guo, Qiaozhen; Wu, Xiaoxu; He, Chengwei; Sang, Xiao; Xie, Tongyao
ABSTRACT: This article verified the error between inversed land surface temperature (LST) and measured LST and developed the modified model based on Landsat 8 remote-sensing data. First, a single-channel algorithm was used to invert the surface temperature using four Landsat 8 remote-sensing images and the LST of the 98 measured points were obtained meantime. Then, the modified model between inversed LST and measured LST was developed based on LST for the 74 measured points. Finally, the developed models were used to modify the inversion temperatures at other 24 measured points, and the mean absolute error (MAE) and mean square error (MSE) between the measured temperature and the inversed temperature before and after the modification were compared to verify the validity of the model. The results showed that the MAE and the MSE of temperature for the 24 measured points used for verification reduced by 0.26 and 0.20 K, respectively, after modification. The development of the modified model can provide an important reference for using Landsat 8 remote-sensing image to invert surface temperature in other regions.